Eksplorasi teknik lampworking pada material kaca berdasarkan ornamen aksesoris baju adat Palembang untuk perhiasan - Aisyah Tiara Syakti; Hendhy Nansha (Institut Seni Indonesia Yogyakarta, 2026)
Lampworking is a technique that involves melting glass at a specific temperature and shaping it while it is molten. This technique is commonly found in fashion products, such as beads. However, it is still rare to find this technique in a large fashion product. A traditional accessory based on Palembang wedding attire would serve as inspiration because the accessories had impressive detail and complicated structure that could be explored with glass. Therefore, this research would testify that the lampworking technique could be implemented on fashion accessories inspired by traditional accessories from Palembang. Started with the exploration of glass shape with lampworking and using metal oxide for colouring the glass. The glass proofed could not produce detailed, shaped, and engraved ornaments like metal. These accessories would be a piece to preserve the culture of Indonesia and introduce the lampworking technique to society. Research that explained the process of lampworking with the result of the glass shape, the colour of the glass, and handling the glass as accessories in fashion is infrequently to be found. Accordingly, this research would help the local artisans who wanted to explore the world of glass. Published Date: 2026-07-22